PENGARUH MEMBIMBING DISKUSI KELOMPOK KECIL TERHADAP KEAKTIFAN BELAJAR AKUNTANSI KEUANGAN KELAS XI AKUNTANSI SMKN 1 POLEWALI - Sapriani Ani; Nuraisyiah; Muhammad Azis (LPPM Universitas Cipta Mandiri, 2024)
This research aims to analyze the influence of skills in guiding small group discussions on activelearning in Financial Accounting subjects in class XI Accounting students at Polewali State VocationalSchool 1. The variables in this research are skills in guiding small group discussions as the independentvariable and active learning as the dependent variable. The population in this study was all students of class The data collection techniques used were questionnaires and documentation. The data analysistechniques used are descriptive statistical analysis, instrument testing, and hypothesis testing usingSPSS Version 25. Based on the results of the data analysis that has been carried out, a simple linear regression equation model Y'=32.935+0.720 From the results of the analysis of the coefficient of determination (r²), thevalue of r² = 0,279 is obtained, which means that the skill of guiding small group discussions influenceto students' active learning by 27.9% and the remaining 72.1% is influenced by other factors.Meanwhile, from the results of the t-test analysis, a significant value of 0.000<0.05 was obtained, whichmeans that the skill of guiding small group discussions has a positive and significant effect on students'active learning, thus the hypothesis is